Scottish Medical Unit : inter-departmental correspondence (copy) - Tewson, Vincent
041-0114-001 H.V. Tewson. Secretary's. Sir Walter Citrine. 5th November, 1936. SCOTTISH MEDICAL UNIT. I understood from Dr. Brook yesterday that Sir Daniel Stevenson has guaranteed £10,000 for the Scottish Medical Unit, and the suggestion was made that any contribution made to the Scottish ambulance would be merely to relieve the responsibilities of Sir Daniel. He further reported that food stuffs and medicaments which had gone out with the unit had not been used and were at present stored in the British Embassy in Madrid. 292/946/41/114